INCREASING THE STUDENTS’ VOCABULARY MASTERY THROUGH JEOPARDY GAME AT THE EIGHTH GRADE OF SMP NEGERI 1 GUNUNGSITOLI BARAT IN 2022/2023 - Zebua, Angelina Pinta Ria; Zebua, Elwin Piarawan; Laoli, Adieli; Maru’ao, Nursayani (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Vocabulary mastery is the ability to use the words in conducting the communication and understanding the meaning of the words or phrases in English. The purpose of the research is to Increase the Students’ Vocabulary Mastery Through Jeopardy Game at the Eighth Grade of SMP Negeri 1 Gunungsitoli Barat which the total numbers of the students was 26 persons. The research was conducted by using Classroom Action Research (CAR) design. This research was applied into two cycles. Each cycle consisted of planning, action, observation, and reflection. The instruments used by the researcher to collect the data were observation sheet, evaluation sheet and field note. From the result of each Cycle, the researcher finds that the students get an improvement in their vocabulary through Jeopardy Game. At the second meeting of cycle II the researcher obtained an increase in students, that students overall reached MCC (70).